Marine Plastics Abatement Technology, Management, Business and Future Trends (Volume 2) - Koottatep, Thammarat; Winijkul, Ekbordin; Wenchao Xue; Atitaya Panuvatvanich; Visvanathan, Chettiyappan; Pussayanavin, Tatchai; Limphitakphong, Nantamol; Chongrak Polprasert (IWA Publishing, 2023)
Marine Plastics Abatement Volume 2 focusses on abatement strategies and up-to-date technological innovations against marine plastic pollution such as resource recovery, plastics-to-values, co-processing, dumpsite recovery, etc. With an understanding of technological solutions and proper management practices, this volume suggests ways to develop businesses from plastic wastes with several cases from developed and developing countries. Furthermore, business case studies are presented along with recent scientific information, and practical exercises together with discussions on future trends such as introduction of biodegradable, or decomposable plastics; product designs for recycling/upcycling; etc.